ENERGY BARS AS FUNCTIONAL FOODS IN MODERN NUTRITION AND INDUSTRIAL DEVELOPMENT - Vinocunga Pillajo, Reni Danilo (Centro Azúcar Journal, 2026)
Introduction: Energy bars have emerged as functional foods that combine convenience and nutritional value, driven by the growing trend toward healthy diets. Objective: To analyze the functional ingredients, nutritional classification, and technological processes used in the production of energy bars. Materials and Methods: A systematic review was conducted following the PRISMA 2020 protocol to ensure rigor and transparency in source selection. The search covered international scientific databases from 2018 to 2025, focusing on formulations, ingredients, and technological processes related to energy bars. Results and Discussion: Formulations containing plant proteins and microalgae improved nutritional quality and sustainability, while cold pressing and extrusion preserved functional compounds more effectively. Conclusions: Energy bars made with natural ingredients and controlled processes provide greater functional value, stability, and consumer acceptance.